Laminated battery cell pole piece structure

By designing specific foil area, coating area and laser line area structures on the lithium-ion laminated battery electrode, the problem of powder dropping off the edge of the electrode plate during punching is solved, and the battery's wetting, heat dissipation performance and stability are improved .

CN222507641UActive Publication Date: 2025-02-18TIANJIN JUYUAN NEW ENERGY TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202421126971.6
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-02-18
Estimated Expiration
2034-05-22

AI Technical Summary

Technical Problem

During the filming process of lithium-ion laminated batteries, the distance between the laser marks or grooves and the edge of the electrode sheet is too close, resulting in powder falling off the edge of the electrode sheet, which in turn affects the battery performance and safety.

Method used

Design a laminated cell electrode structure, including a foil area, a uniformly coated coating area and a laser etching area distributed on the coating area. The width of the laser etching line is 50-200um and the depth is 10-30um. The spacing between the etching lines is 1-3mm, and ensure that the distance between the etching lines and the edge of the pole piece is greater than 2mm.

Benefits of technology

It effectively prevents the problem of powder falling off the edge of the pole sheet during punching, improves the pole sheet wetting and heat dissipation performance of the battery, and improves the stability and electrical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222507641U_ABST
    Figure CN222507641U_ABST
Patent Text Reader

Abstract

The utility model relates to a laminated cell pole piece structure, which comprises a foil material area, a coating area and a laser scribed line area, the coating area is used for uniformly coating a part of the foil material area, the laser scribed line area is distributed on the coating area, a plurality of laser scribed lines are arranged on the laser scribed line area to form a nick structure of a pole piece, the width of each laser scribed line is 50-200 microns, the depth of each laser scribed line is 10-30 microns, and the thickness of each laser scribed line is 10-30 microns. And the distance between the scribed lines is 1-3mm. According to the utility model, the wettability, heat dissipation and cyclic expansion performance of the pole piece of the laminated battery can be effectively improved, other performance and appearance of the battery cannot be influenced, meanwhile, the problem of powder falling of the scribed pole piece can be effectively solved, the stability of the laminated battery is improved, and the laminated battery has remarkable superiority.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of lithium batteries, and in particular to a laminated battery core pole piece structure. Background Art

[0002] As lithium-ion batteries are used more and more widely, lithium-ion laminated batteries are widely used in various electronic devices due to their advantages of high energy density and high power density. In the manufacturing process of lithium-ion laminated batteries, the positive electrode sheet, negative electrode sheet and diaphragm need to be stacked in a certain order, and then fixed together by hot pressing to form the core part of the battery. In this process, due to the high pressure of hot pressing, the positive electrode sheet, negative electrode sheet and diaphragm are tightly bonded, which directly affects the uniformity of the distribution of the electrolyte in the electrode sheet, resulting in poor wettability of the electrode sheet and affecting the battery performance. At the same time, the battery also has the risk of thermal runaway due to excessive heat generation.

[0003] In order to improve the electrode wetting and heat generation problems of lithium-ion laminated batteries, the existing technology is mainly achieved by adopting vacuum standing or changing the electrode structure. For example, the patent document with patent application publication number CN106848187A discloses a method for improving the liquid absorption speed and amount of lithium-ion battery electrode, and the lithium-ion battery is vacuum-standing after liquid injection, and the vacuum standing is continuous vacuum standing or intermittent vacuum standing. The invention adopts the vacuum standing method to shorten the infiltration time of lithium-ion battery electrode, but this method is to evacuate the vacuum after liquid injection, and the electrolyte is easily extracted, which makes the injection amount inaccurate and will contaminate the battery. The patent document with the patent application publication number CN 116830348 A discloses a secondary battery and an electronic device, wherein the secondary battery includes an electrode assembly, the electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator, the separator is arranged between the positive electrode sheet and the negative electrode sheet, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, wherein the surface of the negative electrode active material layer opposite to the positive electrode sheet has a groove, and the depth of the groove is Hμm; the separator includes a substrate layer and a bonding layer, and the thickness of the bonding layer is Tμm, satisfying: H≥T+1. This prior art improves the interface heat dispersion effect of the electrode sheet, enhances the internal heat dissipation capacity, and improves the cycle stability and safety of the lithium-ion battery at high temperature. The patent document with the patent application publication number CN117254128 A discloses a laser-processed lithium-ion battery cell and a battery prepared therefrom, wherein at least one laser-processed area is provided on the positive electrode sheet and / or the negative electrode sheet, and laser drilling or laser scribing is performed in the laser-processed area; when there is more than one laser-processed area on the same electrode sheet, different laser-processing methods are used for each laser-processed area of ​​the electrode sheet: each laser-processed area is a laser-drilling area, and the hole density and / or hole depth of the laser-drilled holes in adjacent laser-drilling areas are different; each laser-processed area is a laser scribing area, and the line density and / or line depth of the laser scribing lines in adjacent laser scribing areas are different; and adjacent laser-processed areas are laser-drilling areas and laser scribing areas, respectively. The invention is a method for laser-processing positive and negative electrode sheets, and can effectively improve the wetting effect of the electrode sheets. However, in the above two methods of processing positive and negative electrodes, when the punching knife is close to the groove / laser mark during the punching process of the laminated battery, powder will fall off the edge of the electrode. The fallen electrode powder will pierce the diaphragm after hot pressing, causing a short circuit, seriously affecting the electrical performance of the battery cell. How to simply and effectively solve the problem of electrode powder falling after laser processing of lithium-ion batteries is still an urgent problem to be solved. Utility Model Content

[0004] The utility model aims to overcome the deficiencies in the prior art and provide a laminated battery core electrode structure, which can solve the problem of powder loss during punching of laser scored / grooved electrodes and effectively improve the electrical performance of the battery core.

[0005] In order to achieve the above-mentioned purpose, the utility model is realized through the following technical scheme: a laminated battery core electrode structure, including a foil area, a coating area where the coating is evenly coated on part of the foil area, and a laser scribing area distributed on the coating area, wherein the laser scribing area is provided with a plurality of laser scribing lines to form a scratch structure of the electrode, the width of the laser scribing lines is 50-200um, the depth is 10-30um, and the scribing line spacing is 1-3mm.

[0006] Furthermore, the coating area is evenly coated on one side or both sides of the foil area.

[0007] Furthermore, the laser engraving lines are placed on one side or both sides of the pole piece.

[0008] Furthermore, the laser engraved lines are arranged along the length direction of the pole piece, along the width direction of the pole piece, or along the diagonal line of the pole piece and in a direction forming an angle θ with the width direction, and the distance between the outermost engraved lines of the laser engraved lines and the edge of the pole piece is greater than 2 mm.

[0009] Furthermore, the spacing between the laser engraved lines along the length direction or the width direction of the pole piece is 1-3 mm, and the distance between the leftmost or rightmost laser engraved line and the edge of the pole piece is ≥2 mm.

[0010] Furthermore, the laser engraved lines arranged in the diagonal direction have a spacing of 1-3 mm, and the distances between the engraved lines diagonally above and below and the four corners of the pole piece are ≥2 mm.

[0011] Furthermore, when the aspect ratio of the pole piece is less than 1, the laser engraving is selected along the length direction of the pole piece or along the diagonal direction of the pole piece.

[0012] Furthermore, when the aspect ratio of the pole piece is 1, the laser engraving is preferably along the diagonal direction of the pole piece.

[0013] Furthermore, when the aspect ratio of the pole piece is greater than 1, the laser engraving is preferably performed along the width direction or along the diagonal direction.

[0014] Furthermore, the depth of the laser engraving line (h) and the thickness of the single-side pole powder (H) are: h=0.2H~0.7H.

[0015] Beneficial effects: Compared with the prior art, the utility model can effectively improve the wettability and heat dissipation performance of the electrode of the laminated battery without affecting other performance and appearance of the battery. At the same time, it can effectively solve the problem of powder loss of the engraved electrode, improve the stability of the laminated battery, and has significant advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic diagram of the structure of Embodiment 1 of the present utility model;

[0017] Figure 2It is a structural schematic diagram of Embodiment 2 of the present utility model;

[0018] Figure 3 It is a structural schematic diagram of Embodiment 3 of the present utility model;

[0019] Figure 4 is the laser scoring trajectory diagram;

[0020] Figure 5 It is the size diagram of the laser-scored trace;

[0021] Figure 6 yes Figure 5 AA view of the .

[0022] In the figure: 1, pole piece, W, the size of the notch from the edge of the pole piece, W1, the width of the laser notch, W2, the spacing between the notch lines, L1, the width of the pole piece, L2, the length of the pole piece, θ, the angle between the notch line and the width of the pole piece, H1, the thickness of the pole powder on one side, h, the depth of the notch. DETAILED DESCRIPTION

[0023] The following is a detailed description of the specific implementation method provided by the utility model in combination with the preferred embodiment: Referring to the accompanying drawings, this embodiment provides a laminated battery cell electrode structure, including a foil area, a coating area uniformly coated on a portion of the foil area, and a laser scribing area distributed on the coating area, wherein the laser scribing area is provided with a plurality of laser scribing lines to form a scratch structure of the electrode, and the width of the laser scribing lines is 50-200um, the depth is 10-30um, and the scribing line spacing is 1-3mm.

[0024] Example 1

[0025] See attached for details Figure 1 , a laminated battery cell pole piece structure, including a foil area, a coating area, and a laser scribing area. The coating area is evenly coated on part of the foil area, and the coating area is evenly coated on at least one side of the foil. The laser scribing is in the form of a single line / multiple lines, evenly / non-evenly distributed on the coating area, and is arranged along the width direction of the pole piece, and the outermost scribing line is greater than 2mm from the edge of the pole piece. The design of the pole piece structure can effectively prevent the problem of pole piece powder shedding caused by the small size of the scribing line and the edge of the pole piece during punching, and effectively improve the electrical performance of the battery cell.

[0026] The preferred solution of this embodiment is that the laser lines are scribed on at least one side of the pole piece.

[0027] Preferably, when the ratio of the pole piece length L2 to the pole piece width L1 is greater than 1, it is preferred to laser scribe lines along the width direction (such as Figure 1 ) or diagonal marking scheme (such as Figure 3 ),

[0028] The preferred solution of this embodiment is that the width w1 and depth h of the laser scribed line can be adjusted according to actual needs to achieve the best wettability and heat dissipation effect. At the same time, the design of the laser scribed line also needs to take into account the safety performance of the battery to avoid the stability of the battery being reduced due to the scribed line being too deep or too wide.

[0029] Preferably, the laser engraving line width w1 is 50-200 um, and the depth h is 10-30 um.

[0030] Preferably, the laser scribing depth h and the single-side pole powder thickness H have the following relationship: h=0.2H~0.7H.

[0031] The preferred solution of this embodiment is that the distance between the laser engraved lines also needs to be adjusted according to actual needs to ensure uniform distribution of the engraved lines. At the same time, the safety performance of the battery also needs to be considered to avoid a decrease in battery stability due to a small distance between the engraved lines.

[0032] In addition, the technical solution sets the distance between the laser scribed line and the edge of the pole piece, as well as the distance between the laser scribed line and the four corners of the pole piece. This ensures that during the punching process of the laminated battery, the laser scribed line will not contact the edge or four corners of the pole piece, thereby avoiding the powder falling from the edge of the pole piece. It can effectively improve the wettability and heat dissipation performance of the pole piece of the lithium-ion laminated battery, and also solve the problem of powder falling from the scribed pole piece, thereby improving the stability of the laminated battery.

[0033] Preferably, the distance between the laser engraving lines arranged along the width direction of the pole piece is 1-3 mm, and the distance between the uppermost or lowermost laser engraving line and the edge of the pole piece is ≥2 mm.

[0034] Example 2

[0035] A laminated battery core pole piece structure includes a foil area, a coating area, and a laser scribing area. The coating area is uniformly coated on part of the foil area, and the coating area is uniformly coated on at least one side of the foil. The laser scribing is in the form of a single line / multiple lines, uniformly / non-uniformly distributed on the coating area, and is arranged along the width direction of the pole piece, and the outermost scribing line is greater than 2 mm from the edge of the pole piece. The design of the pole piece structure can effectively prevent the problem of pole piece powder shedding caused by the small size of the scribing line and the edge of the pole piece during punching, and effectively improve the electrical performance of the battery core.

[0036] The preferred solution of this embodiment is that multiple laser lines are on at least one side of the pole piece. Preferably, when the ratio of the pole piece length L2 to the pole piece width L1 is less than 1, it is preferred to laser line along the length direction (such as Figure 2 ) or laser marking along the diagonal direction (such as Figure 3 ),

[0037] The preferred solution of this embodiment is that the width w1 and depth h of the laser scribed line can be adjusted according to actual needs to achieve the best wettability and heat dissipation effect. At the same time, the design of the laser scribed line also needs to take into account the safety performance of the battery to avoid the stability of the battery being reduced due to the laser scribed line being too deep or too wide.

[0038] Preferably, the laser line width w1 is 50-200 um, and the depth h is 10-30 um.

[0039] Preferably, the laser engraving depth h and the single-sided powder line thickness H have the following relationship: h=0.2H~0.7H. The preferred scheme of this embodiment is that the distance between the laser engraving lines also needs to be adjusted according to actual needs to ensure uniform distribution of the laser engraving lines. At the same time, the safety performance of the battery also needs to be considered to avoid a decrease in battery stability due to a small distance between the laser engraving lines.

[0040] This technical solution sets the distance between the laser scribed line and the edge of the pole piece, as well as the distance between the laser scribed line and the four corners of the pole piece. This ensures that during the punching process of the laminated battery, the laser scribed line will not contact the edge or four corners of the pole piece, thereby avoiding the powder falling off the edge of the pole piece, which can effectively improve the wettability and heat dissipation performance of the pole piece of the lithium-ion laminated battery, and also solve the problem of powder falling off the laser scribed pole piece, thereby improving the stability of the laminated battery.

[0041] Preferably, the distance between the laser engraving lines arranged along the width direction of the pole piece is 1-3 mm, and the distance between the uppermost or lowermost laser engraving line and the edge of the pole piece is ≥2 mm.

[0042] Design principle and advantages of this utility model

[0043] 1. This technical solution can effectively improve the wettability of the pole piece of the laminated battery, thereby improving the performance of the battery. Compared with the existing method of vacuum standing, the line design adopted by this technical solution can increase the uniformity of the distribution of the electrolyte in the pole piece without changing the overall structure of the battery, thereby improving the wettability of the pole piece;

[0044] 2. This technical solution can effectively improve the heat dissipation performance of laminated batteries. Compared with the existing method of setting grooves on the surface of the positive and negative electrodes, this technical solution adopts a line design, which will not cause the edge of the electrode to fall off. It can effectively disperse the interface heat, enhance the internal heat dissipation capacity, and avoid the problem of powder falling off the edge of the electrode caused by setting grooves;

[0045] 3. This technical solution can effectively improve the cycle thickness expansion rate of laminated batteries. Compared with the existing method of setting grooves on the surface of positive and negative electrodes, this technical solution sets the width and depth of the notch, so that when the negative electrode is fully charged and expanded to insert lithium, the notch can fill it horizontally, which can reduce the expansion of the electrode sheet in the thickness direction to a certain extent.

[0046] 4. This technical solution can effectively solve the problem of powder falling from the lined pole piece, thereby improving the stability of the laminated battery. Compared with the existing line-marking technology, this technical solution can more accurately control the position and depth of the line, thereby avoiding the problem of powder falling from the lined pole piece during punching.

[0047] The above-mentioned detailed description of a laminated battery cell pole piece structure with reference to the embodiment is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the utility model should fall within the scope of protection of the utility model.

Claims

1. A laminated battery core electrode structure, comprising a foil area, a coating area in which a coating is evenly coated on a portion of the foil area, and a laser-scribed line area distributed on the coating area, wherein: The laser engraved area is provided with a plurality of laser engraved lines to form the engraved structure of the pole piece. The width of the laser engraved lines is 50-200um, the depth is 10-30um, and the engraved line spacing is 1-3mm.

2. The laminated battery core electrode structure according to claim 1 is characterized in that: The coating area is uniformly coated on one side or both sides of the foil area.

3. The laminated battery core electrode structure according to claim 1 is characterized in that: The laser engraving lines are placed on one side or both sides of the pole piece.

4. The laminated battery core electrode structure according to claim 1 or 3, characterized in that: The laser engraved lines are arranged along the length direction of the pole piece, along the width direction of the pole piece, or along the diagonal line of the pole piece and in the direction of angle θ with the width direction. The distance between the outermost engraved lines of the laser engraved lines and the edge of the pole piece is greater than 2 mm.

5. The laminated battery core electrode structure according to claim 4 is characterized in that: The spacing between the laser engraved lines along the length direction or width direction of the pole piece is 1-3 mm respectively, and the distance between the leftmost or rightmost laser engraved line and the edge of the pole piece is ≥2 mm.

6. The laminated battery core electrode structure according to claim 4 is characterized in that: The laser engraved lines arranged in the diagonal direction have a spacing of 1-3 mm, and the distance between the engraved lines obliquely above and below and the four corners of the pole piece is ≥2 mm.

7. The laminated battery core electrode structure according to claim 1 is characterized in that: When the aspect ratio of the pole piece is less than 1, the laser engraving is selected along the length direction of the pole piece or along the diagonal direction of the pole piece.

8. The laminated battery core electrode structure according to claim 1 is characterized in that: When the aspect ratio of the pole piece is 1, the laser engraving is preferably along the diagonal direction of the pole piece.

9. The laminated battery core electrode structure according to claim 1 is characterized in that: When the aspect ratio of the pole piece is greater than 1, the laser scribing is preferably performed along the width direction or along the diagonal direction.

10. The laminated battery core electrode structure according to claim 1, characterized in that: The depth h of the laser scribing and the thickness H of the single-side pole powder are: h=0.2H~0.7H.

Citation Information

Patent Citations

  • Method capable of improving lithium ion battery pole piece liquid absorption rate and liquid absorption volume

    CN106848187A

  • Secondary battery and electronic device

    CN116830348A

  • Lithium ion cell subjected to laser treatment and battery prepared from lithium ion cell

    CN117254128A